Empowering professional syndicates in Egypt to achieve good governance; An application to the Egyptian Medical Syndicate - Abou Omar, Eissa Mohamed Mohamed (AUC Knowledge Fountain, 2013)
In searching for a governance reform strategy, the size, the vital roles of professional syndicates and their impact on the whole society place them among our top priorities. According to both the old and the new Egyptian constitutions, the professional syndicates have the legal base to represent the different professions, defend rights and interests of their members, improve the quality of the offered services to the society, and share in creating policies and procedures related to syndicates' members and their careers. The discrepancy between the proposed role of the professional syndicates and the reality motivated this research into the reasons behind their weaknesses and poor performance. Little recent analysis of Egypt's syndicates could be found in the literature. Selecting the Egyptian Medical Syndicate (EMS) as a case study was invoked by its vital role in health system reform. The main research question is “To what extent do the governance structure and procedures of the Egyptian Medical Syndicate correspond to international good governance standards?" The qualitative method was adopted in this research. The aspects of the governance of the Canadian Medical Association (CMA) were used as a guide to highlight what components and core compositions of the structures of the EMS should be examined in the governance process and how? In addition, two questionnaires were developed. The first one conducted to the members and the later to senior managers and Board members. The respondents answered these questionnaires through group interview for members and Individual In-Depth Interview for senior managers and Board members. The aim was to make sure through these instruments, it will be possible to assess to what extent the EMS covered the standards principles of good governance and illuminate the areas which need to be improved. The study targeted doctors in three Egyptian governorates (Cairo, Giza and Gharbia) and the sample included males and females from different ages and backgrounds. The research found that the current governance system and procedures are in a bad need to be reformed to be consistent with international good governance standards. The findings of the study illustrated that there is a crucial need to issue a new law and bylaw for the Egyptian Medical Syndicate. The electionsÃ¢â‚¬â„¢ system needs to be revised. There is a necessity to identify a clear vision and mission for the EMS, setting the long term objectives, consider the annual planning and evaluation for the programs and activities. The Board of Directors needs to enhance its leadership and strategic planning skills. The study also highlighted the importance of considering the new tools of communications such as emails, website and video conferences to share information, and to achieve greater connection, participation and involvements for the members of the EMS. This study open the door to further research with hope to develop a good model to evaluate the governance system in other professional syndicates, and it will be possible to apply the model with some adaptation to fit the specific features of each syndicate.